(untitled) (Journal Of Educational and Psychological Researches, 2025)
The study aims to determine the perspective of cochlear implant students’ parents on their children’s education and knowledge construction issues. The study sample consisted of 100 parents of cochlear implant students enrolled in primary schools who are in rehabilitation at the Fayza Organization for the Hearing Impaired and Cochlear Implants, the Continuity of Wellness, and the Cochlear Company, aged 6-16 years; specifically, this age group is the delay in cochlear implantation, which affected the delay in enrollment in primary schools. The researcher used the scale of attitudes towards cognitive construction. The results showed that a cochlear implant is much more effective when a hearing disability has been discovered early; a cochlear implant aims to create sensitivity and speech generation. Family therapy is essential in freeing the individual minor from his imprisonment by a cochlear implant through resolving family relationships that define the home environment, which positively affects school integration.